Coordinated protein co‐expression in plants by harnessing the synergy between an intein and a viral 2A peptide. Issue 6 (30th March 2017) - Zhang, Bei; Rapolu, Madhusudhan; Kumar, Sandeep; Gupta, Manju; Liang, Zhibin; Han, Zhenlin; Williams, Philip; Su, Wei Wen
Summary: A novel approach is developed for coordinated expression of multiple proteins from a single transgene in plants. An Ssp DnaE mini‐intein variant engineered for hyper‐N‐terminal autocleavage is covalently linked to the foot‐and‐mouth disease virus 2A (F2A) peptide with unique ribosome skipping property, via a peptide linker, to create an 'IntF2A' self‐excising fusion protein domain. This IntF2A domain acts, in cis, to direct highly effective release of its flanking proteins of interest (POIs) from a 'polyprotein' precursor in plants. This is successfully demonstrated in stably transformed cultured tobacco cells as well as in different organs of transgenic tobacco plants. Highly efficient polyprotein processing mediated by the IntF2A domain was also demonstrated in lettuce and Nicotiana benthamiana based on transient expression. Protein constituents released from the polyprotein precursor displayed proper function and accumulated at similar levels inside the cells. Importantly, no C‐terminal F2A extension remains on the released POIs. We demonstrated co‐expression of as many as three proteins in plants without compromising expression levels when compared with those using single‐protein vectors. Accurate differential cellular targeting of released POIs is also achieved. In addition, we succeeded in expressing a fully assembled and functional chimeric anti‐His Tag antibody in N. benthamiana leaves. The IntF2A‐based polyprotein transgene system overcomes key impediments of existing strategies for multiprotein co‐expression in plants, which is particularly important for gene/trait stacking.